(untitled) (Comparatismi, 2025)
“No poetic genre has a broader scope than the novel”, wrote Herder, highlighting its capacity to encompass a wide variety of forms and content. Since the emergence of a theory of the novel, it has not merely been conceived as one genre among others, but as a space for redefining the concept of literary genre itself, which is closely linked to the new subjectivity of the Moderns. Early German Romanticism, with its concept of Dichtung as a means of integrating fragments of knowledge, sparked a debate on genres that also served as a tool for historical legitimisation. While Nietzschean readings have often emphasised the nihilistic traits of Romantic thought, this study proposes reconsidering this discussion from Lukács’s perspective, for whom genres are a constant theme. The analysis reveals how certain aspects of Lukács’s work explicitly connect with the Romantic tradition and the theory of literary forms.